2022
DOI: 10.1021/acsomega.2c01810
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Ability of Bio-rejuvenators to Disaggregate Oxidized Asphaltene Nanoclusters in Aged Asphalt

Abstract: A real rejuvenator must have the ability to disaggregate oxidized asphaltene nanoclusters. However, few studies pay attention to the topic, and there is a lack of comparison of the disaggregation ability of different rejuvenators. Thus, the disaggregation ability and regeneration mechanism of three bio-rejuvenators (waste cooking oil (WCO), waste wood oil (WWO), and straw liquefied residue oil (SLRO)) on oxidized asphaltene nanoclusters were studied in this paper. Laboratory tests and molecular dynamics (MD) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…In this paper, the permeability of bio-oils is analyzed by testing the crossover modulus, which has been proved to be related to the dispersion degree of asphaltene and is an evaluation index for quantifying the polydispersity of asphaltene [ 42 , 43 , 44 ]. Our previous research found that both WWO and WCO can increase the crossover modulus, while SLRO can reduce the crossover modulus [ 45 ]. Therefore, comparing the crossover modulus of different PFLs with that of the original aged bitumen can determine the permeation position of the bio-oil in the aged bitumen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, the permeability of bio-oils is analyzed by testing the crossover modulus, which has been proved to be related to the dispersion degree of asphaltene and is an evaluation index for quantifying the polydispersity of asphaltene [ 42 , 43 , 44 ]. Our previous research found that both WWO and WCO can increase the crossover modulus, while SLRO can reduce the crossover modulus [ 45 ]. Therefore, comparing the crossover modulus of different PFLs with that of the original aged bitumen can determine the permeation position of the bio-oil in the aged bitumen.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in most studies, the component or main component with the highest measured content in the test represents the substance [ 23 , 24 , 27 , 57 , 58 ]. In our previous studies, the main components of three bio-oils (WCO, WWO and SLRO) were measured by GC-MS test [ 45 ], and the molecular model of bio-oil was constructed by selecting substances with higher content through analysis. The molecular structures are shown in Figure 22 .…”
Section: Methodsmentioning
confidence: 99%
“…The types and numbers of molecular models for AAA-1 asphalt binder are shown in Table 1. This molecular model has been repeatedly validated in previous studies and has been used to analyze the diffusion [27], selfhealing [28,29], rejuvenation [29] and adhesion [28] of asphalt materials at a nanoscale. Therefore, this model is suitable for molecular dynamics research on the generation and self-healing of nanocracks in asphalt binder systems in this paper.…”
Section: Asphalt Binder Molecular Model Selectionmentioning
confidence: 94%
“…However, neither of those bio-oils could restore the dispersion behavior of aged asphaltenes to the original case. SLRO showed a negative effect on asphaltenes dispersion and was unable to disturb the nanoclusters …”
Section: Chemical Agingmentioning
confidence: 99%
“…SLRO showed a negative effect on asphaltenes dispersion and was unable to disturb the nanoclusters. 157…”
Section: Chemical Agingmentioning
confidence: 99%